Availability and use of ICT in South-Western Nigeria Colleges of Education (2011)
This paper investigated the level of availability and use of ICT in some South-western Nigeria Colleges of Education. The study revealed low level of usage of ICT gadgets and non-availability of some ICT equipments. The data for the study were gathered through a two page questionnaire administered to 200 respondents who were accessible in the School of Education in all the Colleges of Education in the South-Western part of Nigeria. In total, 180 questionnaires were retrieved which represents 90% return rate. At the same time, the data were analyzed quantitatively using SPSS. The results of the survey on College of Education staff on the level of availability, use of and perception of the impact of ICT on teacher education in Nigeria revealed and suggested a low level of usage of ICT gadgets; nonavailability of ICT equipment and that the respondents were disgruntled with the sluggish use and integration of ICT.